Islamic Educational Transformation: A Study of Scientific and Competence Development in the Study Program of Islamic Education in State Islamic Universities - Usman; Fuad, Moch; Munajat, Nur (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2017)
The research is descriptive and evaluative about religion and modernization of education for the purpose of finding and describing new problems regarding the basic framework of scientific and curriculum development at PAI Studies Program. The purpose of this study is to describe and reveal indicators of the basic framework changes, the views, and attitudes of academicians, curriculum development, and learning process that mainly based on information technology. The research was conducted on three State Islamic Universities, namely UIN Sunan Kalijaga Yogyakarta, UIN Syarif Hidayatullah Jakarta, and UIN Maulana Malik Ibrahim Malang with subject research Faculty of Tarbiyah and Teaching Sciences or PAI study program, and sampling technic was done by purposive random. The data was collected by observation method of participation, structured and in-depth interviews, and questionnaire method to faculty (leader) and students. Data analysis was performed through the logical interpretation and constant comparation. This research is conducted in the field by collecting data, writing, and provide a logical interpretation of the data. Based on data and analysis above, it can be concluded that implementation of scientific development conducted by study programs/majors PAI to realize an integrated-interconnection approach is already reflected in the determination of the base (vision and mission) majors, policies (quality objectives or quality assurance), programs, and learning process. The whole has grown, when it is understood from the meaning of modernization of education (change/development model of education management), from the old way/conventional leads to a more contemporary.